1999
DOI: 10.1055/s-0037-1614622
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection and the Risk of Myocardial Infarction: Role of Fibrinogen and Its Genetic Control

Abstract: SummaryThe contribution of Helicobacter pylori (HP) infection to the risk of myocardial infarction was evaluated. The role of fibrinogen and its genetic control as a possibile mechanism by which HP may influence myocardial infarction risk was explored in this context. A case-control study was performed in 101 patients with myocardial infarction and in 101 controls.HP infection was associated with an increased risk of myocardial infarction independently for confounding variables (OR 4.1, CI95: 1.8-9.4). HP infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…46 Zito et al 16 showed that the BclI polymorphisms of ␤-fibrinogen gene modulated the effect of HP on both fibrinogen levels and the risk of myocardial infarction. HP, a life-long bacterial infection, was found to be associated with chronically increased plasma levels of fibrinogen.…”
Section: Gene-environment Interactions and Risk Of Cardiovascular Dismentioning
confidence: 99%
See 2 more Smart Citations
“…46 Zito et al 16 showed that the BclI polymorphisms of ␤-fibrinogen gene modulated the effect of HP on both fibrinogen levels and the risk of myocardial infarction. HP, a life-long bacterial infection, was found to be associated with chronically increased plasma levels of fibrinogen.…”
Section: Gene-environment Interactions and Risk Of Cardiovascular Dismentioning
confidence: 99%
“…The rare B2B2 genotype has been consistently associated with levels of fibrinogen 15% to 20% higher than that of the B1B1 genotype. [12][13][14][15][16] However, because of its location on the gene, it would be difficult to consider a biological function for this polymorphism, which has been mainly considered as a marker for another locus on the fibrinogen gene.…”
Section: Genetic Determinants Of Fibrinogen Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies demonstrated that the bacteria disrupted interstitial and intravascular cell to cell interactions, leading to marked microvascular dysfunction [32]. Furthermore, it is probably associated with increased levels of fibrinogen [33], and platelet activation and aggregation [34], other processes implicated in the microvascular dysfunction and inflammatory-cell recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these polymorphic sites have been reported as being associated with the risk for cardiovascular disease (de Maat et al, 1995;de Maat et al, 1997;van der Bom et al, 1997;Weiss et al, 1996;Zito et al, 1999;Di Castelnuovo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%